2020
DOI: 10.3389/fnins.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotactile Sensory Feedback Improves Embodiment of a Prosthetic Hand During Active Use

Abstract: There have been several advancements in the field of myoelectric prostheses to improve dexterity and restore hand grasp patterns for persons with upper limb loss, including robust control strategies, novel sensory feedback, and multifunction prosthetic terminal devices. Although these advancements have shown to improve prosthesis performance, a key element that may further improve acceptance is often overlooked. Embodiment, which encompasses the feeling of owning, controlling and locating the device without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…These movements are functionally important for individuals with transradial amputation [37]. Notably, the hand open and close movements were not included in this study, given that wrist flexion and extension can instead be used to control the opening and closing of a prosthetic hand [31], [38]- [41]. Similarly, forearm pronation and supination can be used to control prosthetic wrist rotation.…”
Section: Data Collectionmentioning
confidence: 99%
“…These movements are functionally important for individuals with transradial amputation [37]. Notably, the hand open and close movements were not included in this study, given that wrist flexion and extension can instead be used to control the opening and closing of a prosthetic hand [31], [38]- [41]. Similarly, forearm pronation and supination can be used to control prosthetic wrist rotation.…”
Section: Data Collectionmentioning
confidence: 99%
“…This finding is consistent with contemporary work by Shehata et al . 39 , where tapping was used to induced ownership of a passive prosthesis worn by able-bodied participants. Furthermore, we showed that a small stimulation area was sufficient for a successful RHI.…”
Section: Discussionmentioning
confidence: 99%
“…Additional straps can be mounted to add additional mounting points. These mounting points could also be used to integrate sensory feedback systems, such as mechanotactile tactors [5] , [23] and vibrotactile tactors [13] , [24] (see Figure 3 ). Interior Cushions: Cushions provide a compliant fit to conform with and support the wearer’s residual limb.…”
Section: Methodsmentioning
confidence: 99%